Differential effects of a tertiary individual prevention programme for patients with occupational skin disease depending on diagnosis - Matterne, Uwe; Diepgen, Thomas L.; Weisshaar, Elke (Journal of the European Academy of Dermatology and Venereology, 2010)
Occupational skin disease (OSD) is common. Tertiary individual prevention programmes (TIP) aim at helping individuals with refractory OSD to remain active in the workforce. Evidence exists that these interventions improve skin protection behaviour related cognitions. However, it is not clear whether these effects generalize to all types of OSD. Objective To evaluate whether effects on socio-cognitive determinants of skin protection behaviour vary between patients with work related atopic dermatitis (AD) and other work related skin diseases.
Gesehen am 25.05.2023